Tony Bellotti - interview, Radio France - Bellotti, T. (2011)
CIAT entomologist and cassava expert Tony Bellotti speaking on Radio France Internationale, following the release of a CIAT study into the potential hotspots for combined outbreaks of cassava pests and diseases across the tropics.